Implementation of Exclusive Breastfeeding Education for Postpartum Mothers at Maccini Sawah Community Health Centre, Makassar City - Wulandari, Fani; Limbong, Magdalena; Kasim, Erna; Nurbaiti, Nurbaiti (LPPM STIKes Muhammadiyah Ciamis, 2025)
Exclusive breastfeeding is breast milk given to babies under 6 months Mother's knowledge about exclusive breastfeeding is an understanding of the benefits, techniques of giving, and the importance of exclusive breastfeeding for the health of the mother and baby Mothers' knowledge about exclusive breastfeeding is an understanding of the benefits, techniques for giving, and the importance of exclusive breastfeeding for the health of mothers and babies. This case study was conducted with the aim of evaluating how education related to exclusive breastfeeding is implemented and to what extent it has an impact on increasing the knowledge of postpartum mothers in the working area of the Macini Sawah Community Health Centre, Makassar City. This case study design uses a descriptive approach with a case study method. The case study in this research focuses on exploring the implementation of education on exclusive breastfeeding and its impact on the level of knowledge of postpartum mothers in the working area of the Maccini Sawah Community Health Centre, Makassar City. In this case study, data was collected using an observation form aimed at assessing the level of knowledge among postpartum mothers. The observation form was filled out directly by the respondents using paper and pen. The results of observations for 3 days showed the effectiveness of providing exclusive breastfeeding education to postpartum mothers, the level of maternal knowledge increased. After conducting a case study, it was concluded that the implementation of exclusive breastfeeding on postpartum mothers' knowledge increased after the action was given.